Rehabilitation of degraded areas in northeastern Patagonia, Argentina: Effects of environmental conditions and plant functional traits on performance of native woody species - Zeberio, Juan Manuel (2020)
Degradation processes affect a vast area of arid and semi-arid lands around the world and damage the environment and people’s health. Degradation processes are driven by human productive activities that cause direct and indirect effects on natural resources, such as species extinction at regional scale, reduction and elimination of vegetation cover, soil erosion, etc. In this context, ecological rehabilitation is an important tool to recover key aspects of the degraded ecosystem. Rehabilitation trials rely on the use of native plant species with characteristics that allow them to obtain high survival and growth rates. The aim of this work was to assess the survival and growth of native woody species in degraded areas of northeastern Patagonia and relate them to plant functional traits and environmental variables. We observed high early and late survival rates, and growth rates in Prosopis flexuosa DC. var. depressa F.A. Roig and Schinus johnstonii F.A. Barkley, and low values in Condalia microphylla Cav. and Geoffroea decorticans (Gillies ex Hook. & Arn.) Burkart. Early survival rates were positively associated with specific leaf area (SLA) and precipitation, but negatively associated with wood density, the maximum mean temperature of the warmest month and the minimum mean temperature of the coldest month. Late survival rates were positively associated with SLA and soil organic matter, but negatively associated with plant height and precipitation. The temperature had a positive effect on late survival rates once the plants overcame the critical period of the first summer after they were transplanted to the field. Prosopis flexuosa and S. johnstonii were the most successful species in our study. This could be due to their functional traits that allow these species to acclimatize to the local environment. Further research should focus on C. microphylla and G. decorticans to determine how they relate to productive conditions, acclimation to environmental stress, auto-ecology and potential use in ecological rehabilitation trials.